Izrazno-pomenska tipologija poimenovanj - Vidovič-Muha, Ada (Slavistična revija, 2007)
The formal-semantic analysis of lexicon with respect to the presentation of the denotatum displays three basic types, i.e., lexical items are sentence elements or set phrases, word-classes with grammatical meaning, but without being sentence constituents, lexicalized speech acts with possible pragmatic circumstances, constitutive components of speech acts, and clausal sentence. -Linguistic-cultural aspect is limited to the presentation of the formal typology of denotation.
Keywords: denotat; denotative capacity of language; denotatum; jezikovna kultura; language culture; poimenovalna zmožnost jezika; semantics; semantika; Slovene langugae; slovenščina